Gender dan Kekuatan Sosial : Analisis Antropologi Terhadap Peran Wanita Dalam Masyarakat Tradisional Minangkabau: Gender and Social Power: Anthropological Analysis of the Role of Women in Traditional Minangkabau Society - Dewi, Cantika (DEMOS: Journal of Demography, Ethnography and Social Transformation, 2024)
This article examines the role of women in traditional Minangkabau society through a social anthropology perspective, focusing on gender dynamics and social power intertwined within the matrilineal structure. Although Minangkabau women have a strong position in the management of family heirlooms and customs, they still face patriarchal influences that hinder their role in formal leadership and political decisions. The method used in this research is qualitative literature, by analyzing various literatures that include theories of matrilineality, gender, and social structure in Minangkabau society. This research reveals the tension between traditional values that support the central role of women and patriarchal challenges that still exist in various aspects of social life. The results are expected to provide insights into how Minangkabau women navigate their roles amidst social change and modernization that affect their cultural order.